1994
DOI: 10.3109/17453679408993718
|View full text |Cite
|
Sign up to set email alerts
|

Gait after knee arthroplasty for femoral tumor: Foot pressure patterns recorded in 20 patients

Abstract: We evaluated pressure distribution patterns under the feet during gait in 20 patients after resection of malignant bone tumor and endoprosthetic replacement of the distal femur. In all cases, a modular cementless, hinged prosthesis had been used. The examination was performed after 4 (1-6) years. Shortened contact phase, decreased peak pressure, and reduced force-time integral during gait analysis were observed on the operated side. Peak pressure in the heel and the toe regions was decreased and the load (forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…These patterns have been studied by various authors (Otis et al 1985, McClenhaghan et al 1989, Harris et al 1990, Tsuboyama et al 1994, Catani et al 1996, De Visser et al 1998, Kawai et al 1998, De Visser et al 1999. In 1988, Simon noted that patients who had had a limb salvage procedure differed greatly in gait compensation, which made interpretation of gait analysis dif cult.…”
Section: Discussionmentioning
confidence: 95%
“…These patterns have been studied by various authors (Otis et al 1985, McClenhaghan et al 1989, Harris et al 1990, Tsuboyama et al 1994, Catani et al 1996, De Visser et al 1998, Kawai et al 1998, De Visser et al 1999. In 1988, Simon noted that patients who had had a limb salvage procedure differed greatly in gait compensation, which made interpretation of gait analysis dif cult.…”
Section: Discussionmentioning
confidence: 95%
“…Kinetic assessments have shown that these patients exhibit shortened contact phases, decreased peak vertical ground reaction forces and reduced internal knee moment generation during stance [8,13,18,19], suggesting attempts to minimise stress on their affected lower limb (L A ) and shift weight to their unaffected lower limb (L U ).…”
Section: Introductionmentioning
confidence: 99%
“…Tsuboyama et al studied a similar patient group and showed that asymmetry was caused by a shortened contact phase, decreased peak pressure, and reduced force-time integral during gait on the affected side. 5 Furthermore, a positive correlation was found between load under the foot and isokinetically measured knee extension strength. de Visser et al 4 found that the stance phase of the affected leg was similar to the stance phase of a normal population and that the stance phase of the nonaffected leg was lengthened.…”
Section: Discussionmentioning
confidence: 90%
“…2 When gait pattern has changed from normal, patients try to gain more stability at the cost of flexibility. 4,5 Because gait is less automatic, these patients use more energy for normal walking as compared with a healthy population. The amount of energy depends on the extensiveness of the resection.…”
mentioning
confidence: 99%